(untitled) (Pulse, 2018)
Anterior mediastinal teratomas are rare germ cell tumors. We report a case of such rare tumor in a 16 years old boy who presented with sudden severe right sided abdominal pain which radiating to chest for one day. CT scan of the chest was suggestive of anterior mediastinal teratoma. Patient underwent Clamshell thoracotomy. Peroperatively a large mass was found in the anterior mediastinum containing huge amount of sebum like material. It was adherent to mediastinal surface of right & left lung, pericardium and great vessels (SVC, Aorta). The tumor and was resected out except part of its posterior surface which was adherent to pericardium and great vessels and was left in situ. He had a smooth & uneventful post-operative recovery. Histopathology reported as mature (benign) teratoma with no evidence of malignancy. Pulse Vol.10 January-December 2017 p.52-56